A high-precision ceramic material for semiconductor and preparation method thereof
By adopting ceramic materials with specific ratios and preparation processes, the strength, toughness, dielectric loss and porosity of existing high-precision ceramic materials for semiconductors has been solved, and the comprehensive performance of ceramic materials has been improved.
Patent Information
- Application Number
- CN202411338453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing high-precision ceramic materials for semiconductors have technical defects such as insufficient strength, insufficient toughness, large dielectric loss and high porosity.
A method for preparing a ceramic material including a matrix component, a sintering additive, a sub-component, a reinforcing component and a bonding component is adopted. The matrix component is Ba-Ti-Bi-rare earth element-Zr-A-M-O, the sub-components are nanoniobium silicide, nanotantalum carbide, nanogallium nitride, the reinforcement component is nanoboronitride fiber, and the bonding component includes liquid polyborosilazane and PVA 098-05 binder. By reasonably selecting process parameters and raw material ratios, the strength, fracture toughness, dielectric loss and porosity of the material are improved.
It realizes high strength, foot fracture toughness, low dielectric loss and low porosity of ceramic materials, and is suitable for high precision applications of semiconductor equipment and has high promotion and application value.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor ceramic materials, and in particular to a semiconductor high-precision ceramic material and a preparation method thereof. Background Art
[0002] The upgrade and iteration of semiconductor equipment depends largely on key technological breakthroughs in precision parts. Precision parts are not only one of the more difficult and technically demanding links in semiconductor equipment manufacturing, but also one of the "bottleneck" links in domestic semiconductor equipment, supporting the entire semiconductor chip manufacturing and modern electronic information industry. In recent years, the semiconductor industry has developed rapidly, the scale of the industry has increased rapidly, semiconductor manufacturing equipment has continued to evolve towards precision and complexity, and the technical requirements for key components of high-precision ceramics have become increasingly higher. It can be seen that it is imperative to develop high-precision ceramic materials for semiconductors with excellent comprehensive performance and performance stability.
[0003] Existing semiconductor high-precision ceramic materials still have more or less insufficient strength, insufficient toughness, large dielectric loss, high apparent porosity and other technical defects. In order to solve the above problems, the Chinese invention patent with authorization announcement number CN116332630B is a method for preparing alumina ceramics for semiconductor equipment. The method uses alumina and magnesium fluoride as raw materials and is prepared by simple mixing-ball milling-injection-granulation-molding-sintering process. The invention adjusts the content of magnesium fluoride between each layer of ceramic and the thickness of each layer, combined with the optimization of process parameters, so that the sintering aids of the upper and lower layers in the alumina ceramic are completely released, thereby improving the corrosion resistance of the ceramic. The ceramic has a high density, good compactness, low grain size, strong connectivity between the internal layers, and excellent mechanical strength. At the same time, the material thickness is controllable and adjustable, and the preparation and acquisition of large-size ceramic materials can also be realized. This ceramic sintered material can be used to make various key components of semiconductor vacuum manufacturing equipment. However, the toughness of the ceramic material needs to be further improved, and the dielectric loss and apparent porosity need to be further reduced.
[0004] It can be seen that the development of a high-precision ceramic material for semiconductors with high strength, sufficient fracture toughness, low dielectric loss and apparent porosity and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of high-precision ceramic materials for semiconductors. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high-precision ceramic material for semiconductors having high strength, sufficient fracture toughness, low dielectric loss and apparent porosity, and a preparation method thereof.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 55-75 parts of a matrix component, 3-5 parts of a sintering aid, 8-12 parts of a subsidiary component, 10-20 parts of a reinforcing component, and 1-3 parts of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:(0.1-0.3); M is at least one of In, Fe, Co, Mo, and Ta; the subsidiary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:(0.8-1.2):(0.3-0.5).
[0007] Preferably, the preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid to water, mixing them evenly, and spray drying them to obtain a precursor, then calcining the precursor, taking it out and grinding it, and passing it through a 500-800 mesh sieve to obtain the matrix component.
[0008] Preferably, the barium source is at least one of barium chloride and barium nitrate; the titanium source is at least one of titanium chloride and titanium nitrate; the bismuth source is bismuth (III) acetate; and the rare earth source is scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate mixed in a mass ratio of 1:(0.3-0.5):(0.5-0.8):(0.1-0.3).
[0009] Preferably, the zirconium source is at least one of zirconium chloride and zirconium nitrate; the A source includes sodium borate and sodium tellurite; and the M source is at least one of indium nitrate, iron nitrate, cobalt nitrate, molybdenum nitrate and tantalum ethoxide.
[0010] Preferably, the mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05:(0.08-0.12):1:0.02:(0.1-0.2):0.7:(10-16).
[0011] Preferably, the calcination temperature is 550-820° C. and the calcination time is 3-5 h.
[0012] Preferably, the sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:(0.1-0.3); the particle size of the sintering aid is 500-800 mesh.
[0013] Preferably, the particle size of the secondary component is 10-80 nm.
[0014] Preferably, the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 100-200 nm, and the aspect ratio is (20-30):1.
[0015] Preferably, the bonding component comprises the following raw materials in parts by weight: 3-5 parts of liquid polyborosilazane and 40-60 parts of PVA 098-05 adhesive.
[0016] Preferably, there is no special requirement for the source of the liquid polyborosilazane. In one embodiment of the present invention, the liquid polyborosilazane is prepared according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0017] Another object of the present invention is to provide a method for preparing the semiconductor high-precision ceramic material, comprising the following steps:
[0018] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 500-800 mesh sieve to obtain a uniform powder;
[0019] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 3-5 hours, then performing debinding and shaping in sequence to obtain a green body;
[0020] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0021] Preferably, the ball media for ball milling in step S1 are zirconium balls, and the ball milling solvent is ethanol.
[0022] Preferably, the debinding in step S2 is carried out in a vacuum environment, the debinding temperature is 460-560°C, and the debinding time is 1-3h; the shaping pressure is 10-15MPa, the temperature is 220-320°C, and the insulation time is 2-4 hours.
[0023] Preferably, the sintering treatment in step S3 adopts two-stage sintering, the first stage sintering temperature is 850-950° C., firing for 1-3 hours, and the second stage sintering temperature is 1560-1800° C., firing for 4-10 hours.
[0024] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0025] (1) The method for preparing high-precision ceramic materials for semiconductors disclosed in the present invention does not require special equipment, requires little capital investment, has a simple process flow, is easy to control production conditions, has strong operability, is suitable for large-scale production, and has high promotion and application value.
[0026] (2) The semiconductor high-precision ceramic material disclosed in the present invention comprises the following raw materials in parts by weight: 55-75 parts of matrix component, 3-5 parts of sintering aid, 8-12 parts of auxiliary component, 10-20 parts of reinforcing component, and 1-3 parts of bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:(0.1-0.3); M is at least one of In, Fe, Co, Mo, and Ta; the auxiliary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:(0.8-1.2):(0.3-0.5). Through the mutual coordination and joint action of the raw materials, the prepared ceramic material has high strength, sufficient fracture toughness, low dielectric loss and apparent porosity, and has broad application prospects in the field of semiconductor high-precision ceramic materials.
[0027] (3) The high-precision ceramic material for semiconductor disclosed in the present invention uses raw materials with various particle sizes and different sintering dynamics, which can effectively improve the sintering effect, increase the internal density of the material, make the apparent porosity lower, and increase the strength and toughness. The bonding component includes the following raw materials in parts by weight: 3-5 parts of liquid polyborosilazane and 40-60 parts of PVA 098-05 adhesive; the use of the bonding component with the above composition formula can better improve the compatibility between the raw materials; the reasonable selection of other raw material types and dosage ratios can further improve the strength and fracture toughness and reduce the dielectric loss.
[0028] (4) The high-precision ceramic material for semiconductors disclosed in the present invention can effectively improve the strength, fracture toughness, dielectric loss and apparent porosity of the material by rationally selecting the process parameters during the preparation process, thereby effectively extending its service life. DETAILED DESCRIPTION
[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0030] Embodiment 1, a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 55 parts of a matrix component, 3 parts of a sintering aid, 8 parts of a subsidiary component, 10 parts of a reinforcing component, and 1 part of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:0.1; M is In; the subsidiary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:0.8:0.3.
[0031] The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 500-mesh sieve to obtain a matrix component; the barium source is barium chloride; the titanium source is titanium chloride; the bismuth source is bismuth (III) acetate; the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:0.3:0.5:0.1; the zirconium source is zirconium chloride; the A source comprises sodium borate and sodium tellurite; and the M source is indium nitrate.
[0032] The mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05:0.08:1:0.02:0.1:0.7:10; the calcination temperature is 550°C and the time is 3h; the sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:0.1; the particle size of the sintering aid is 500 mesh; the particle size of the subcomponent is 10nm; the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 100nm, and the aspect ratio is 20:1; the bonding component includes the following raw materials in parts by weight: 3 parts of liquid polyborosilazane and 40 parts of PVA 098-05 adhesive; the liquid polyborosilazane is made according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0033] A method for preparing the semiconductor high-precision ceramic material comprises the following steps:
[0034] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 500-mesh sieve to obtain a uniform powder;
[0035] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 3 hours, then performing debinding and shaping in sequence to obtain a green body;
[0036] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0037] The ball medium of the ball mill described in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding described in step S2 is carried out in a vacuum environment, the debinding temperature is 460°C, and the debinding time is 1h; the shaping pressure is 10MPa, the temperature is 220°C, and the insulation time is 2 hours; the sintering treatment described in step S3 adopts two-stage sintering, the first stage sintering temperature is 850°C, the firing is 1h, and the second stage sintering temperature is 1560°C, and the firing is 4h.
[0038] Embodiment 2, a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 60 parts of a matrix component, 3.5 parts of a sintering aid, 9 parts of a subsidiary component, 12 parts of a reinforcing component, and 1.5 parts of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:0.15; M is Fe; the subsidiary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:0.9:0.35.
[0039] The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 600-mesh sieve to obtain a matrix component; the barium source is barium nitrate; the titanium source is titanium nitrate; the bismuth source is bismuth (III) acetate; the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:0.35:0.6:0.15; the zirconium source is zirconium nitrate; the A source comprises sodium borate and sodium tellurite; and the M source is ferric nitrate.
[0040] The mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05:0.09:1:0.02:0.13:0.7:12; the calcination temperature is 650°C and the time is 3.5h; the sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:0.15; the particle size of the sintering aid is 600 mesh; the particle size of the subcomponent is 30nm; the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 130nm, and the aspect ratio is 22:1; the bonding component includes the following raw materials in parts by weight: 3.5 parts of liquid polyborosilazane and 45 parts of PVA 098-05 adhesive; the liquid polyborosilazane is made according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0041] A method for preparing the semiconductor high-precision ceramic material comprises the following steps:
[0042] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 600-mesh sieve to obtain a uniform powder;
[0043] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 3.5 hours, then performing debinding and shaping in sequence to obtain a green body;
[0044] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0045] The ball medium of the ball mill described in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding described in step S2 is carried out in a vacuum environment, the debinding temperature is 490°C, and the debinding time is 1.5h; the shaping pressure is 12MPa, the temperature is 240°C, and the insulation time is 2.5 hours; the sintering treatment described in step S3 adopts two-stage sintering, the first stage sintering temperature is 870°C, the firing time is 1.5h, and the second stage sintering temperature is 1590°C, and the firing time is 5h.
[0046] Embodiment 3, a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 65 parts of a matrix component, 4 parts of a sintering aid, 10 parts of a sub-component, 15 parts of a reinforcing component, and 2 parts of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:0.2; M is Co; the sub-component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:1:0.4.
[0047] The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 650-mesh sieve to obtain a matrix component; the barium source is barium chloride; the titanium source is titanium nitrate; the bismuth source is bismuth (III) acetate; the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:0.4:0.65:0.2; the zirconium source is zirconium chloride; the A source comprises sodium borate and sodium tellurite; and the M source is cobalt nitrate.
[0048] The mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05:0.1:1:0.02:0.15:0.7:13; the calcination temperature is 660°C and the time is 4h; the sintering aid is a mixture of alumina and hafnium boride in a mass ratio of 1:0.2; the particle size of the sintering aid is 650 mesh; the particle size of the subcomponent is 50nm; the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 150nm, and the aspect ratio is 25:1; the bonding component includes the following raw materials in parts by weight: 4 parts of liquid polyborosilazane and 50 parts of PVA 098-05 adhesive; the liquid polyborosilazane is made according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0049] A method for preparing the semiconductor high-precision ceramic material comprises the following steps:
[0050] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 700-mesh sieve to obtain a uniform powder;
[0051] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 4 hours, then performing debinding and shaping in sequence to obtain a green body;
[0052] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0053] The ball medium of the ball mill described in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding described in step S2 is carried out in a vacuum environment, the debinding temperature is 520°C, and the debinding time is 2h; the shaping pressure is 13MPa, the temperature is 280°C, and the insulation time is 3 hours; the sintering treatment described in step S3 adopts two-stage sintering, the first stage sintering temperature is 900°C, the firing time is 2h, and the second stage sintering temperature is 1680°C, and the firing time is 7h.
[0054] Embodiment 4, a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 73 parts of a matrix component, 4.5 parts of a sintering aid, 11 parts of a sub-component, 18 parts of a reinforcing component, and 2.5 parts of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:0.25; M is a mixture of In, Fe, Co, Mo, and Ta in a mass ratio of 1:2:1:1:0.3; the sub-component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:1.1:0.45.
[0055] The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through a 750-mesh sieve to obtain a matrix component; the barium source is a mixture of barium chloride and barium nitrate in a mass ratio of 1:3; the titanium source is a mixture of titanium chloride and titanium nitrate in a mass ratio of 3:5; the bismuth source is bismuth (III) acetate; the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:0.45:0.75:0.25; the zirconium source is a mixture of zirconium chloride and zirconium nitrate in a mass ratio of 1:2; the A source comprises sodium borate and sodium tellurite; the M source comprises indium nitrate, iron nitrate, cobalt nitrate, molybdenum nitrate and tantalum ethoxide.
[0056] The mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05: 0.11:1:0.02:0.18:0.7:15; the calcination temperature is 810°C and the time is 4.5h; the sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:0.25; the particle size of the sintering aid is 750 mesh; the particle size of the subcomponent is 70nm; the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 190nm, and the aspect ratio is 28:1; the bonding component includes the following raw materials in parts by weight: 4.5 parts of liquid polyborosilazane and 55 parts of PVA 098-05 adhesive; the liquid polyborosilazane is made according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0057] A method for preparing the semiconductor high-precision ceramic material comprises the following steps:
[0058] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 780-mesh sieve to obtain a uniform powder;
[0059] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 4.5 hours, then performing debinding and shaping in sequence to obtain a green body;
[0060] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0061] The ball medium of the ball mill described in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding described in step S2 is carried out in a vacuum environment, the debinding temperature is 550°C, and the debinding time is 2.5 hours; the shaping pressure is 14MPa, the temperature is 310°C, and the insulation time is 3.5 hours; the sintering treatment described in step S3 adopts two-stage sintering, the first stage sintering temperature is 940°C, the firing time is 2.5 hours, and the second stage sintering temperature is 1780°C, and the firing time is 9 hours.
[0062] Embodiment 5, a high-precision ceramic material for semiconductors, comprising the following raw materials in parts by weight: 75 parts of a matrix component, 5 parts of a sintering aid, 12 parts of a subsidiary component, 20 parts of a reinforcing component, and 3 parts of a bonding component; the matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:0.3; M is Ta; the subsidiary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:1.2:0.5.
[0063] The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out, grinding it, and passing it through an 800-mesh sieve to obtain a matrix component; the barium source is barium nitrate; the titanium source is titanium chloride; the bismuth source is bismuth (III) acetate; the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:0.5:0.8:0.3; the zirconium source is zirconium chloride; the A source comprises sodium borate and sodium tellurite; and the M source is tantalum ethoxide.
[0064] The mass ratio of the barium source, titanium source, bismuth source, rare earth source, zirconium source, A source, M source, citric acid and water is 0.3:0.1:0.05:0.12:1:0.02:0.2:0.7:16; the calcination temperature is 820°C and the time is 5h; the sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:0.3; the particle size of the sintering aid is 800 mesh; the particle size of the subcomponent is 80nm; the reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 200nm, and the aspect ratio is 30:1; the bonding component includes the following raw materials in parts by weight: 5 parts of liquid polyborosilazane and 60 parts of PVA 098-05 adhesive; the liquid polyborosilazane is made according to the method of Example 4 of the Chinese invention patent with authorization announcement number CN105694048B.
[0065] A method for preparing the semiconductor high-precision ceramic material comprises the following steps:
[0066] Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through an 800-mesh sieve to obtain a uniform powder;
[0067] Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 5 hours, then performing debinding and shaping in sequence to obtain a green body;
[0068] Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
[0069] The ball medium of the ball mill described in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding described in step S2 is carried out in a vacuum environment, the debinding temperature is 560°C, and the debinding time is 3 hours; the shaping pressure is 15MPa, the temperature is 320°C, and the insulation time is 4 hours; the sintering treatment described in step S3 adopts two-stage sintering, the first stage sintering temperature is 950°C, the firing time is 3 hours, and the second stage sintering temperature is 1800°C, and the firing time is 10 hours.
[0070] Comparative Example 1, a high-precision ceramic material for semiconductors and a preparation method thereof, is basically the same as Example 1, except that Bi, Te and nano-tantalum carbide are not added.
[0071] Comparative Example 2, a high-precision ceramic material for semiconductors and a preparation method thereof, is substantially the same as Example 1, except that In, B and liquid polyborosilazane are not added.
[0072] In order to further illustrate the beneficial technical effects of the high-precision ceramic materials for semiconductors involved in each embodiment of the present invention, relevant performance tests were performed on the high-precision ceramic materials for semiconductors involved in Examples 1-5 and Comparative Examples 1-2; the test methods are as follows:
[0073] (1) Bending strength: refer to GB / T 4741-1999 for bending strength test;
[0074] (2) Fracture toughness: Tested according to the three-point bending test in accordance with GB / T 23806-2009;
[0075] (3) Dielectric loss: obtained through testing with a vector network analyzer and a dielectric properties test operating platform;
[0076] (4) Apparent porosity: The test was conducted in accordance with GB / T 25995-2010. The test results are shown in Table 1.
[0077]
[0078] As can be seen from Table 1, the high-precision ceramic materials for semiconductors involved in the embodiments of the present invention have better flexural strength and fracture toughness, lower apparent porosity and dielectric loss than the comparative products. The combined use of Bi, Te, nano-tantalum carbide, In, B and liquid polyborosilazane is beneficial to improving the above properties.
[0079] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-precision ceramic material for semiconductors, characterized in that: The invention comprises the following raw materials in parts by weight: 55-75 parts of matrix component, 3-5 parts of sintering aid, 8-12 parts of auxiliary component, 10-20 parts of reinforcing component and 1-3 parts of bonding component; The matrix component is Ba-Ti-Bi-rare earth element-Zr-AMO, wherein A is a mixture of B and Te in a mass ratio of 1:(0.1-0.3); M is at least one of In, Fe, Co, Mo, and Ta; and the secondary component is a mixture of nano-niobium silicide, nano-tantalum carbide, and nano-gallium nitride in a mass ratio of 1:(0.8-1.2):(0.3-0.5); The preparation method of the matrix component comprises the following steps: adding a barium source, a titanium source, a bismuth source, a rare earth source, a zirconium source, an A source, an M source and citric acid into water, mixing them evenly, spray drying them to obtain a precursor, then roasting the precursor, taking it out and grinding it, passing it through a 500-800 mesh sieve to obtain a matrix component; the A source comprises sodium borate and sodium tellurite; the mass ratio of the barium source, the titanium source, the bismuth source, the rare earth source, the zirconium source, the A source, the M source, citric acid and water is 0.3:0.1:0.05:(0.08-0.12):1:0.02:(0.1-0.2):0.7:(10-16); The sintering treatment of the semiconductor high-precision ceramic material adopts two-stage sintering, the first stage sintering temperature is 850-950°C, the sintering time is 1-3h, and the second stage sintering temperature is 1560-1800°C, the sintering time is 4-10h.
2. The high-precision ceramic material for semiconductor according to claim 1, characterized in that: The barium source is at least one of barium chloride and barium nitrate; the titanium source is at least one of titanium chloride and titanium nitrate; the bismuth source is bismuth acetate; and the rare earth source is a mixture of scandium nitrate, yttrium nitrate, praseodymium nitrate and dysprosium nitrate in a mass ratio of 1:(0.3-0.5):(0.5-0.8):(0.1-0.3).
3. The high-precision ceramic material for semiconductor according to claim 1, characterized in that: The zirconium source is at least one of zirconium chloride and zirconium nitrate; the M source is at least one of indium nitrate, iron nitrate, cobalt nitrate, molybdenum nitrate and tantalum ethoxide.
4. The high-precision ceramic material for semiconductor according to claim 1, characterized in that: The calcination temperature is 550-820° C. and the calcination time is 3-5 hours.
5. The high-precision ceramic material for semiconductor according to claim 1, characterized in that: The sintering aid is a mixture of aluminum oxide and hafnium boride in a mass ratio of 1:(0.1-0.3); the particle size of the sintering aid is 500-800 mesh; and the particle size of the secondary component is 10-80 nm.
6. The high-precision ceramic material for semiconductor according to claim 1, characterized in that: The reinforcing component is nano boron nitride fiber, the average diameter of the reinforcing component is 100-200nm, and the aspect ratio is (20-30):1; the bonding component includes the following raw materials in parts by weight: 3-5 parts of liquid polyborosilazane and 40-60 parts of PVA 098-05 adhesive.
7. A method for preparing a high-precision ceramic material for semiconductor according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, after mixing the other raw materials except the bonding component uniformly by weight, adding them into a ball mill for ball milling, drying them after the ball milling, and passing them through a 500-800 mesh sieve to obtain a uniform powder; Step S2, putting the uniform powder obtained in step S1 into a low-speed stirring tank, adding a bonding component into the low-speed stirring tank and stirring for 3-5 hours, then performing debinding and shaping in sequence to obtain a green body; Step S3: sintering the green body to obtain a high-precision ceramic material for semiconductor.
8. The method for preparing a high-precision ceramic material for semiconductor according to claim 7, characterized in that: The ball medium of the ball mill in step S1 is zirconium ball, and the ball milling solvent is ethanol; the debinding in step S2 is carried out under vacuum environment, the debinding temperature is 460-560°C, and the debinding time is 1-3h; the shaping pressure is 10-15MPa, the temperature is 220-320°C, and the insulation time is 2-4 hours.
Citation Information
Patent Citations
Preparation method of polyborosilazane adhesive
CN105694048B
A method for preparing alumina ceramics for semiconductor devices
CN116332630B
Nanometer composite ceramic material and preparation method and application thereof
CN116283307A
Preparation method of aluminum oxide ceramic for semiconductor equipment
CN116332630A